Olaparib With or Without Cediranib Versus Platinum-Based Chemotherapy in Recurrent Platinum-Sensitive Ovarian Cancer (NRG-GY004): A Randomized, Open-Label, Phase III Trial. Issue 19 (1st July 2022) - Liu, Joyce F.; Brady, Mark F.; Matulonis, Ursula A.; Miller, Austin; Kohn, Elise C.; Swisher, Elizabeth M.; Cella, David; Tew, William P.; Cloven, Noelle G.; Muller, Carolyn Y.; Bender, David P.; Moore, Richard G.; et al.
Abstract : PURPOSE: Platinum-based chemotherapy is the standard of care for platinum-sensitive ovarian cancer, but complications from repeated platinum therapy occur. We assessed the activity of two all-oral nonplatinum alternatives, olaparib or olaparib/cediranib, versus platinum-based chemotherapy. PATIENTS AND METHODS: NRG-GY004 is an open-label, randomized, phase III trial conducted in the United States and Canada. Eligible patients had high-grade serous or endometrioid platinum-sensitive ovarian cancer. Patients were randomly assigned 1:1:1 to platinum-based chemotherapy, olaparib, or olaparib/cediranib. The primary end point was progression-free survival (PFS) in the intention-to-treat population. Secondary end points included activity within germline BRCA -mutated or wild-type subgroups and patient-reported outcomes (PROs). RESULTS: Between February 04, 2016, and November 13, 2017, 565 eligible patients were randomly assigned. Median PFS was 10.3 (95% CI, 8.7 to 11.2), 8.2 (95% CI, 6.6 to 8.7), and 10.4 (95% CI, 8.5 to 12.5) months with chemotherapy, olaparib, and olaparib/cediranib, respectively. Olaparib/cediranib did not improve PFS versus chemotherapy (hazard ratio [HR] 0.86; 95% CI, 0.66 to 1.10; P = .077). In women with germline BRCA mutation, the PFS HR versus chemotherapy was 0.55 (95% CI, 0.32 to 0.94) for olaparib/cediranib and 0.63 (95% CI, 0.37 to 1.07) for olaparib. In women without a germline BRCA mutation, the PFS HR versus chemotherapy was 0.97 (95% CI, 0.73 to 1.30) for olaparib/cediranib and 1.41 (95% CI, 1.07 to 1.86) for olaparib. Hematologic adverse events occurred more commonly with chemotherapy; however, nonhematologic adverse events were higher with olaparib/cediranib. In 489 patients evaluable for PROs, patients receiving olaparib/cediranib scored on average 1.1 points worse on the NFOSI-DRS-P subscale (97.5% CI, –2.0 to –0.2, P = .0063) versus chemotherapy; no difference between olaparib and chemotherapy was observed. CONCLUSION: Combination olaparib/cediranib did not improve PFS compared with chemotherapy and resulted in reduced PROs. Notably, in patients with a germline BRCA mutation, both olaparib and olaparib/cediranib had significant clinical activity. Abstract :